Philosophy Concept of Restorative Justice in Handling Juvenile Delinquent - Isma Nurillah; Dian Afrilia; Neisa Angrum Adisti; Desia Rakhma Banjarani (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
Restorative justice in handling juvenile delinquent occurs because of the juvenile justice system growth. The increasing number of institutions that guarantee the rights of children in juvenile delinquent at the courts has led more implementation of the criminal justice system that applies restorative justice. Alignment between the 2000 UN declaration as the main principles regarding the use of restorative justice programs in criminal matters, the Vienna Declaration on crime and justice, the XI UN congress in 2005 on crime and criminal justice as a basis for researchers who passionate to examine how philosophical concept of restorative justice in juvenile delinquent and how the mechanism for applying restorative justice in juvenile delinquent uses normative juridical research. After conducting research, the philosophical concept of restorative justice in handling juvenile delinquent can be seen from before the rise of Law Number 3 of 1997 concerning Juvenile Court which refers to the provisions of the Criminal Code Articles 45, 46, and 47 which contain the authority of judges in making decisions regarding types of crimes, types of punishment and the length of punishment for children, Law Number 3 of 1997 concerning Juvenile Court and Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. In line with the philosophy of the mechanism for the application of restorative justice in handling juvenile delinquent, there are several regulations in Indonesia such as the Supreme Court Regulation Number 4 of 2014 concerning Guidelines for Implementing Diversion in the Juvenile Criminal Justice System, Government Regulation Number 65 of 2015 concerning Guidelines for Implementing Diversion and Handling of Children who have not 12 years old and a certificate from the Director General of Badilum Number 1691/DJU/SK/PS.00/12/2020 dated 22 December 2020 concerning Guidelines for the Implementation of Restorative Justice in the General Courts.